Analisis Peningkatan Jumlah Nasabah Di PT Valbury Asia Futures Melalui Electronic Word Of Mouth - Hendriyani, Chandra; Cecilia Ashari Tanudarma; Fenny Damayanti (SKeTsa Bisnis (e-jurnal), 2023)
English Version The trend of futures trading companies is experiencing a shift where many investors who previously invested in other instruments are starting to switch to the futures trading industry. Valbury Asia Futures Bandung as a futures trading company continues to try to increase the number of customers and build a corporate image through electronic word of mouth (e-WOM) activities. However, Valbury Asia Futures, which has been trying to increase the number of customers and build the company's image, has also been negatively affected by the issue of investment abuse from cases in Indonesia such as the Doni Salmanan case. In early 2022, CoFTRA and Kominfo blocked sites for illegal futures trading where they did not have a permit. The research method used is descriptive qualitative method with data collection techniques from journals, books and reports. The results showed that e-WOM in the form of corporate social media, websites and the Member get Member system resulted in an increase in the number of customers with the dominant indicator influencing the increase in the number of customers was content rather than social media. E-WOM used by Valbury Asia Futures has a positive effect on customer interest and purchasing decisions, where E-WOM is formed from 4 (four) factors, namely expressing positive feelings, economics incentives, helping the company and concern for others. The advice that can be given is that Valbury Asia Futures Bandung must be more creative in creating publications on social media. Versi Indonesia Tren perusahaan perdagangan berjangka sedang mengalami shifting dimana banyak investor yang tadinya berinvestasi pada instrumen lain mulai beralih ke industri perdagangan berjangka. Valbury Asia Futures Bandung sebagai perusahaan perdagangan berjangka terus berusaha menambah jumlah nasabah serta membangun citra perusahaan melalui kegiatan electronic word of mouth (e-wom). Namun, Valbury Asia Futures yang sudah berusaha menambah jumlah nasabah serta membangun citra perusahaan tersebut turut terdampak negatif akibat isu penyalahgunaan investasi dari kasus-kasus yang ada di Indonesia seperti kasus Doni Salmanan. Di awal tahun 2022 lalu Bappebti bersama Kominfo memblokir situs-situs perdagangan berjangka illegal dimana mereka tidak memiliki ijin. Metode penelitian yang digunakan adalah metode kualitatif deskriptif dengan teknik pengumpulan data dari jurnal, buku dan laporan. Hasil penelitian menunjukkan e-WOM dengan bentuk sosial media perusahaan, website dan sistem Member get Member menghasilkan peningkatan jumlah nasabah dengan indikator dominan yang mempengaruhi peningkatan jumlah nasabah adalah konten daripada sosial media. E-WOM yang digunakan oleh Valbury Asia Futures berpengaruh positif terhadap minat dan keputusan pembelian oleh nasabah, dimana E-WOM ini terbentuk dari 4 (empat) faktor yaitu expressing positive feelings, economics incentives, helping the company dan concern for others. Saran yang dapat diberikan adalah agar Valbury Asia Futures Bandung harus lebih kreatif dalam menciptakan publikasi di sosial media.